Increasing occurrence of cold and warm extremes during the recent global warming slowdown - Nathaniel C. Johnson (Nature Portfolio, 2018)
During 2002–2014, global mean temperatures stayed nearly steady, but both summertime warm and wintertime cold extreme temperature occurrences over North Hemisphere continents increased. Here the authors show that the contrasting changes in these metrics were driven by distinct climate patterns.